CTK-like syndrome: Corneal opacity and flattening following sequential intracorneal ring implantation and corneal cross-linking - Bruno M. Fontes; Ricardo M. Nosé; Farhad Hafezi; Emilio A. Torres-Netto (American Journal of Ophthalmology Case Reports)
Purpose: This is a case report of a 31-year-old male patient presenting progressive and markedly asymmetric keratoconus treated with sequential intracorneal ring segment (ICRS) implantation followed by accelerated corneal cross-linking (CXL). Observations: The follow-up after the last procedure revealed a thin, opacified cornea with an unexpected massive flattening of up to 20.3 D. The central flattening attributed to the individual effect of CXL (post-ICRS-implant vs. post-CXL) was 19.1 D. Conclusions and Importance: This original case reports how CXL followed by ICRS implant may result in an early and extreme corneal remodeling. Moreover, such an unusual combination of extreme corneal flattening, thinning, and opacification may imitate a clinical manifestation of central toxic keratopathy and suggests that eyes with ICRS implantation must be followed closely if CXL is performed sequentially after.